Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) terhadap Hasil Belajar Matematika Siswa Kelas IV - Endang Sulistianingsih; Izzah Fijriyah (Mataram University, 2026)
This study aims to determine the influence of the Numbered Heads Together (NHT) type cooperative learning model on Student Learning Outcomes in Grade IV Mathematics Subjects at SDN Mlajah 2 Bangkalan. This study is a quantitative research with a quasi-experimental design, and the form of research design used is a non-equivalent control group design. The population in the study is the entire fourth grade of SDN Mlajah 2 Bangkalan which totals 89 students. The sample used in the study was class IV of SDN Mlajah 2 consisting of 45 students in grades IV-A and 44 students in grades IV-B. The sampling technique in the study used non-probability sampling with saturated sampling techniques. The data collection technique in this study uses observation and learning outcome tests. The test instruments used in this study first went through validity, reliability, difficulty, and differentiating power. The pre-trial test used was a normality test with the Shapiro wilk technique and a homogeneity test. Hypothesis test using an independent sample t-test. Based on the results of the analysis of the t-test data, the independent sample t-test obtained a sig (2-tailed) value obtained < 0.00 < 0.05, then Ho was rejected. Therefore, it can be concluded that there is an influence of the Numbered Heads Together (NHT) type Cooperative Learning Model on Student Learning Outcomes in Grade IV Mathematics Subjects at SDN Mlajah 2 Bangkalan.